2013
DOI: 10.1227/neu.0b013e318270d010
|View full text |Cite
|
Sign up to set email alerts
|

Practice Makes Perfect? The Role of Simulation-Based Deliberate Practice and Script-Based Mental Rehearsal in the Acquisition and Maintenance of Operative Neurosurgical Skills

Abstract: Despite significant advances in technology and intraoperative techniques over the last century, operations on the brain and spinal cord continue to carry a significant risk of serious morbidity or mortality. Potentially avoidable technical errors are well recognized as contributing to poor surgical outcome. Surgical education is undergoing overwhelming change, in part as a result of changes in the economic, political, social, cultural, and technological climates in which it operates. Shortened training, reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 29 publications
0
28
0
2
Order By: Relevance
“…The regular application of imagery with 30 surgical trainees in urogynecology by the author led to high satisfaction among trainees who indicated that imagery sessions were among the most valuable training elements of their rotation. Imagery has also been proposed for the practice of uncommon neurosurgical procedures before performing them on patients, 11 as a low-cost educational supplement for surgical simulation training in neurosurgery, 12 and as a method of facilitating deliberate practice by rehearsing specific tasks to overcome weaknesses in performance. implemented an imagery intervention with novices, and found that participants who received physical suturing practice followed by guided imagery training performed statistically equal to controls who received additional physical practice when suturing a live rabbit model.…”
Section: Mental Imagerymentioning
confidence: 99%
See 1 more Smart Citation
“…The regular application of imagery with 30 surgical trainees in urogynecology by the author led to high satisfaction among trainees who indicated that imagery sessions were among the most valuable training elements of their rotation. Imagery has also been proposed for the practice of uncommon neurosurgical procedures before performing them on patients, 11 as a low-cost educational supplement for surgical simulation training in neurosurgery, 12 and as a method of facilitating deliberate practice by rehearsing specific tasks to overcome weaknesses in performance. implemented an imagery intervention with novices, and found that participants who received physical suturing practice followed by guided imagery training performed statistically equal to controls who received additional physical practice when suturing a live rabbit model.…”
Section: Mental Imagerymentioning
confidence: 99%
“…Imagery has been shown to be a cost-effective training supplement to physical practice that cuts down on resource consumption, [12][13]17,23,29,31 and enhances surgeons' performance through improved acquisition and performance of surgical skills, [13][14][15][16][18][19]22,24,[29][30] knowledge, 11,23,26 confidence, 23,[26][27] and team-based skills. 25 …”
Section: Mental Imagerymentioning
confidence: 99%
“…It was completed by 231 residents (65%) and all 11 PDs (100%) for an overall response rate of 67%. Response rates varied by individual program, ranging from a low of 30% to a high of 100% for the 11 When comparing means of two groups, variables were considered to be continuous and normally distributed, and a Student's t-test was used to determine statistical significance (ie, all residents to PDs). Analysis of variance was used when comparing means of normally distributed continuous variables among three groups (ie, interns to juniors to seniors).…”
Section: Methodsmentioning
confidence: 99%
“…Although the development of expertise had been studied extensively in disciplines such as athletics, music, and other arts for some time, it is only within the last few years that its value has become increasingly recognized within the medical community [5,6]. Many fields such as internal medicine, emergency medicine, and general surgery have studied the importance of deliberate practice in transforming learners into experts, but little has been published regarding its role in creating expert orthopedic surgeons [4,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…2,23 In a continuing effort to improve training, the Dreyfus paradigm has been adapted in neurosurgical training, whereby a trainee rises from novice to expert, passing through graduated levels. 7,19 Although time and observation are characteristics of this progression, neither can substitute for hands-on repetition and staged practice.…”
mentioning
confidence: 99%